Pensions, Debt and Inflation Risk in a Monetary Union - Yvonne Adema (Tinbergen Institute, 2010)
This paper investigates the international spillovers of government debt and the associated risk of inflation within a monetary union when countries have different pension systems. I use a stochastic two-country two-period overlapping-generations model, where one country has PAYG pensions and the other country has funded pensions. The paper shows that the PAYG country can shift part of its long-term debt burden to the funded country. Moreover, the PAYG country gains from unexpected inflation at the cost of the funded country. In response to these conflicting interests about inflation, inflation risk may rise with the level of debt in the PAYG country. Higher inflation risk harms both countries. Actually, in contrast to the debt burden, the PAYG country cannot share the negative effects of a rise in inflation risk with the funded country. The scenarios analysed might be especially relevant for the years to come.
Keywords: E31; F41; G11; G12; H55; H63; 330; spillovers; pensions; debt; inflation; Haushaltsdefizit; Spillover-Effekt; Inflation; Währungsunion; Overlapping Generations; Zwei-Länder-Modell; Theorie